Reference values for hydration biomarkers: optimizing athletic performance and recovery - Armstrong, L. E.; Stearns, R. L.; Huggins, R. A.; Sekiguchi, Y.; Mershon, A. J.; Casa, D. J. (Open Access Journal of Sports Medicine, 2025)
The negative effects of dehydration or overhydration on exercise performance and health are widely recognized. However, the interindividual variability of fluid imbalances among athletes and across various sports is large, due to the complex interactions of physiological, environmental, and sport-specific factors. Such complexity not only makes it difficult to predict fluid needs prior to competition or training sessions, but also supports the creation of an individualized hydration plan (IHP) for each athlete. Measurements of valid, field-expedient biomarkers such as body mass change, urine concentration, and thirst enable ongoing monitoring of an athlete`s hydration state and are integral components of an IHP. Unfortunately, no extensive repository of sport-relevant hydration biomarker data exists. Therefore, this narrative review presents a novel inventory of pre- and post-exercise reference values for body mass change, urine specific gravity, and subjective rating of thirst. These reference values were identified via electronic database searches that discovered field studies of competitive events, weight category sports, training sessions, and routine daily activities. We propose that comparing an athlete`s real-time body mass change, urine specific gravity, and thirst rating to previously published reference values will clarify the extent of dehydration or overhydration, guide rehydration efforts, and optimize subsequent exercise performance, recovery, and health.